PENGGUNAAN MEDIA BUKA KOTAK PADA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS IV SDN 6 PADANG SIBUSUK KECAMATAN KUPITAN KABUPATEN SIJUNJUNG - Rinawanti Rinawanti (Adiba Aisha Amira, 2024)
This study aims to improve the learning outcomes of Islamic Religious Education (PAI) of fourth grade students of SDN 6 Padang Sibusuk, Kupitan District, Sijunjung Regency, by utilizing Word Wall media through the